Forecasting Fish Product Export in Tamilnadu – A Stochastic Model Approach - Sankar*, T. Jai (Recent Research in Science and Technology, 2011)
This study aims at forecasting fish product export in Tamilnadu, based on data on inland and marine fish product export during the years from 1969 to 2008. The study considered Autoregressive (AR), Moving Average (MA) and Autoregressive Integrated Moving Average (ARIMA) processes to select the appropriate stochastic model for forecasting fish product export in Tamilnadu. Based on ARIMA (p, d, q) and its components ACF, PACF, Normalized BIC, Box-Ljung Q statistics and residuals estimated, ARIMA (0, 1, 2) was selected. Based on the chosen model, it could be predicted that the fish product export would increase to 1, 14,695 tons in 2015 from 74,549 tons in 2008 in Tamilnadu.